. Association of Antioxidant Markers (SOD, GSH, NO, Catalase) with Ischemic Stroke Severity and Recovery Outcomes: Markers (SOD, GSH, NO, Catalase) with Ischemic Stroke Severity - Shengxian, Wu (Journal of Medical Biochemistry, 2025)
Objective: The aim of this study was to investigate the relationship between antioxidant markers (Superoxide Dismutase [SOD], Glutathione [GSH], Catalase, and Nitric Oxide [NO]) and the severity of ischemic stroke in affected individuals. Methods: A randomized controlled, single-blind study was conducted from June 2022 to November 2024. The study included 364 patients aged 45-80 years diagnosed with ischemic stroke. Participants were randomly divided into two groups: Group A (n=193) received standard stroke rehabilitation therapy, while Group B (n=171) received additional antioxidant support. Serum levels of SOD, GSH, Catalase, and NO were measured. The severity of ischemic stroke was evaluated using the modified Rankin Scale (mRS) and NIH Stroke Scale (NIHSS), with follow-up evaluations conducted at 2-, 4-, and 6-months post-treatment.Results: Among the 364 participants, 203 (55.7%) were male, and 161 (44.3%) were female, with a mean age of 67.3 ± 12.2 years. Serum SOD levels were higher in the experimental group (16.3 ± 3.7 U/mL) compared to the control group (12.5 ± 4.1 U/mL, p = 0.014). GSH levels were also significantly higher in the experimental group (178 ± 31 μmol/L) than in the control group (145 ± 26 μmol/L, p = 0.032). NO levels were higher in the experimental group (42.1 ± 8.6 μmol/L) than in the control group (35.4 ± 7.3 μmol/L, p = 0.021). Catalase levels were 52.3 ± 11.1 U/mL in the experimental group and 49.6 ± 10.2 U/mL in the control group, with no significant difference between the groups (p = 0.213). Significant inverse correlations were found between SOD, GSH, and NO levels and stroke severity (p < 0.05), but catalase showed no such correlation (p = 0.513).Conclusion: This study identified a significant relationship between lower levels of SOD, GSH, and NO and more severe ischemic stroke outcomes. Higher levels of these antioxidants were associated with improved recovery. In contrast, catalase did not show a significant association with stroke severity or recovery, suggesting that SOD, GSH, and NO may play a more critical role in the pathophysiology of ischemic stroke.
Keywords: Ischemic stroke, Antioxidant markers, Superoxide Dismutase, Glutathione, Catalase, Nitric Oxide, Stroke severity, Recovery outcomes